Juízes(as) negros(as) e seus modos de julgar: processos educativos, lugar de fala e engrenagem institucional - Eduardo Levi de Souza (2019)
This Master's Dissertation, titled: Black Judges and Their Modes to Judge: educational processes, place of speech and institutional change, investigated the connections between the educational processes and of sociability experienced by black judges, in different spaces and times, and the conceptions about racial relations and the repercussions in the way they claim to judge cases in the scope of the First Instance of Minas Gerais Court of the district court of Belo Horizonte. In this sense, the performance of black judges in processes involving issues related to the field of ethnic-racial relations, and their interface with the formative processes through which they have passed and the possible reflexes in the way they judge in their final decisions, in which there is a debate on the merits of the demand brought to the judiciary - became the starting point for this research. To achieve the objective proposed by the research: to understand how the identity of the interviewed black judges is constructed, and if there is any connection with the way they claim to judge. The research method adopted was the semistructured interview. From the analyzes made and based on the interviews with the subjects of research, in constant dialogue with theoretical references, we came to final considerations, which in true open a door and do not end the research, whow the past os the judges are decisive factors to the decisions, as well as the assimilation of the colonial and racialized legal culture. Thus, considering the racial belonging of black judges, in this current frame of the composition of the Brazilian Legal Court, which it is characterized and structured / composed of the men white, there is a tendency that those can judge according to the custom already in force and colonized by the Judiciary. This is what I call institutional change in favor of erasing differences.